On the path to translation: Highlights from the 2010 Canadian Conference on Ovarian Cancer Research - Thériault Brigitte L; Shepherd Trevor G (BMC, 2011)
Abstract Ovarian cancer continues to be the most lethal of the gynaecologic malignancies due to the lack of early detection, screening strategies and ineffective therapeutics for late-stage metastatic disease, particularly in the recurrent setting. The gathering of researchers investigating fundamental pathobiology of ovarian cancer and the clinicians who treat patients with this insidious disease is paramount to meeting the challenges we face. Since 2002, the Canadian Conference on Ovarian Cancer Research, held every two years, has served this essential purpose. The objectives of this conference have been to disseminate new information arising from the most recent ovarian cancer research and identify the most pressing challenges we still face as scientists and clinicians. This is best accomplished through direct encounters and exchanges of innovative ideas among colleagues and trainees from the realms of basic science and clinical disciplines. This meeting has and continues to successfully facilitate rapid networking and establish new collaborations from across Canada. This year, more guest speakers and participants from other countries have extended the breadth of the research on ovarian cancer that was discussed at the meeting. This report summarizes the key findings presented at the fifth biennial Canadian Conference on Ovarian Cancer Research held in Toronto, Ontario, and includes the important issues and challenges we still face in the years ahead to make a significant impact on this devastating disease.